Needle gauge and patient pain in steroid injection of the knee: a prospective randomized controlled trial - Schwartz, John T.; Hatter, Matthew J.; Harrington, Justin; Saito, Rex; Sidhu, Jaspreet S.; Huish, Eric G. (International Journal of Research in Orthopaedics, 2026)
Background: Intra-articular corticosteroid injection (IACI) is a common conservative treatment modality for knee osteoarthritis (OA) but can cause procedural discomfort. Needle gauge is a modifiable factor that may influence patient pain perception, though evidence remains limited. This study compared 18- versus 22-gauge needles in knee IACIs. Methods: The authors performed a single-blinded, prospective, randomized controlled trial at a public teaching hospital (San Joaquin General Hospital, in French Camp, CA) from May 10, 2023 to October 16, 2024. Adults with primary knee OA indicated for corticosteroid injection were randomized to receive injection with either an 18-gauge or 22-gauge needle. All injections were performed via the superolateral approach using triamcinolone acetonide and lidocaine. Pain scores were measured using a visual analogue scale (VAS). Secondary outcomes included anticipated pain, nervousness, and satisfaction. Results: Twenty-six patients were randomized (14 in the 18-gauge group, 12 in the 22-gauge group). Median injection pain was similar between groups (median 2.5 vs 2.5, p=0.71). Post-injection pain was lower in the 18-gauge group (median 1.5 vs 3.5, p=0.21), but not statistically significant. Pre-injection nervousness correlated with both injection pain (ρ=0.50, p=0.011) and post-injection pain (ρ=0.55, p=0.004). Conclusions: Needle gauge did not significantly affect pain or satisfaction during knee IACIs. Psychosocial factors appear to play a greater role in pain perception than needle size.